Equal image quality and reduced radiation exposure in whole-spine X-ray imaging with slot-scanning technique compared with stitched radiography - Liebscher, Hendrik; Scherzer, Mechthild; Meißner, Christoph; Zwingenberger, Stefan; Platz, Uwe; Hahlbohm, Patricia; Schön, Felix; Kühn, Jens-Peter; Hoffmann, Ralf-Thorsten; Blum, Sophia Freya Ulrike (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2025)
Repeated whole-spine imaging in children and adolescents with scoliosis causes significant cumulative radiation exposure. Low-dose slot-scanning imaging can reduce radiation exposure. The aim of this study was to compare whole-spine imaging using the slot-scanning technique (SST) with conventional stitched radiography (SR) with regard to image quality and radiation dose.We recruited 30 patients with a clinical indication for whole-spine imaging by SST, who had prior whole-spine imaging by SR available. 41 images acquired using both techniques were analyzed. The dose area product (DAP) and patient age, weight, height, and body-mass index were recorded. Image quality was assessed for 28 anatomical landmarks on a 4-point Likert scale by 4 raters. Group-wise comparisons were performed using paired t-tests. Interrater rating reliability was assessed using the interrater correlation coefficient.The mean DAP was significantly lower for SST than for SR (SST 8.0 ± 5.7 cGy · cm², SR 32.5 ± 34.5 cGy · cm², p < 0.001). The image quality was rated good for both modalities (means: SST 2.8 ± 0.6, SR 2.7 ± 0.5, p = 0.38). There was no significant difference in image quality ratings between both modalities. The inter-rater reliability was excellent with an inter-rater correlation coefficient of 0.86. Orthopedic surgeons rated the image quality of SST significantly better than that of SR.This study shows a significant reduction in radiation exposure for slot-scanning whole-spine imaging compared to stitched radiography with equal image quality, which facilitates the reduction of radiation exposure for repeated whole-spine imaging in children and adolescents to 25%.
Keywords: slot-scanning technique; scoliosis; whole-spine imaging; ALARA; pediatric radiographs; dose area product